2019
DOI: 10.1111/andr.12707
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics analysis of seminal plasma in patients with idiopathic Oligoasthenoteratozoospermia using high‐resolution NMR spectroscopy

Abstract: Background Male infertility is a global health issue caused by a combination of different factors. Specialists generally rely on semen analysis to diagnose male infertility. However, it is known that diagnostic semen analysis fails to identify about 50% of male infertility disorders. Recently, metabolomics has been proven to be a powerful technique for the diagnosis of different diseases. Objective To determine whether metabolites could be used as potential biomarkers for the diagnosis of male factor infertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
54
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 43 publications
5
54
2
Order By: Relevance
“…Our data shows that the pig SP is comprised by 19 metabolites, which include amino acids, salts, nucleosides, and other organic compounds. The 1 H NMR spectra obtained for pig SP is similar to that of human SP, with all identified metabolites in pig SP also present in human SP [33,38,39]. In some of these human studies, a higher number of spectral peaks (between 31-33 peaks) and metabolites were identified compared with the results reported here, which could be due to differences in the preparation of SP samples, or in the 1 H NMR spectrometer used [33,38].…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Our data shows that the pig SP is comprised by 19 metabolites, which include amino acids, salts, nucleosides, and other organic compounds. The 1 H NMR spectra obtained for pig SP is similar to that of human SP, with all identified metabolites in pig SP also present in human SP [33,38,39]. In some of these human studies, a higher number of spectral peaks (between 31-33 peaks) and metabolites were identified compared with the results reported here, which could be due to differences in the preparation of SP samples, or in the 1 H NMR spectrometer used [33,38].…”
Section: Discussionsupporting
confidence: 60%
“…The 1 H NMR spectra obtained for pig SP is similar to that of human SP, with all identified metabolites in pig SP also present in human SP [33,38,39]. In some of these human studies, a higher number of spectral peaks (between 31-33 peaks) and metabolites were identified compared with the results reported here, which could be due to differences in the preparation of SP samples, or in the 1 H NMR spectrometer used [33,38]. The similarity between pig and human SP metabolite composition was surprising considering their different proteomic profiles [7,20].…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In our study, the altered levels of choline in the seminal plasma of patients with oligozoospermia compared to control class suggested an altered choline metabolism associated with this pathological condition. Muncu et al [46] analyzed a cohort of patients with oligoasthenoteratozoospermia (OAT) by high-resolution 1 H NMR spectroscopy to reveal the metabolomic changes of seminal plasma compared to a control class. The levels of citrate, choline, spermine, putrescine, α-ketoglutaric acid, valine, and tyrosine were significantly different between the two groups.…”
Section: Discussionmentioning
confidence: 99%